Mucormycosis in lung transplant recipients: A systematic review of the literature and a case series. Issue 2 (9th January 2020) - Wand, Ori; Unterman, Avraham; Izhakian, Shimon; Fridel, Ludmila; Kramer, Mordechai R.
Abstract: Background: Mucormycosis is a rare infection in lung transplant recipients (LTR). Our objective was to better define the clinical presentation and optimal management of this frequently lethal infection. Methods: A systematic review of the literature was performed to identify all published cases of mucormycosis in LTR using PubMed/MEDLINE. These cases were analyzed together with a new case series from our clinic. Results: Literature search yielded 44 articles matching the inclusion criteria, describing 121 cases. Six additional cases were identified from our clinic. Data regarding infection site and outcome were available for a total of 53 patients. The lungs were the most common site of infection (62%), followed by rhinocerebral and disseminated disease. Most cases (78%) developed in the first post‐transplant year, with over 40% of them in the first month. Additional risk factors for mucormycosis were identified in over half of the patients. Surgical debridement was uncommon in pulmonary infection (9%). Posaconazole therapy was used in 35% of cases, mostly in combination with amphotericin B. Overall mortality was 32% but varied according to site of infection. Conclusion: Mucormycosis in LTRs tends to be an early post‐surgical infection, associated with additional risk factors and intensified immunosuppressive states, and most often affects the lungs, where surgical debridement is rarely feasible. Posaconazole as first‐line therapy should be further explored.